Språkutveckling i förskolan : En kvalitativ studie om hur pedagoger arbetar med att stödja barns språkutveckling i förskolan - Karlsson, Sara; Markstedt, Anna (2013)
Anna Markstedt and Sara Karlsson (2012) Language development in preschool, a qualitative study on how teachers work to support children's language development in preschool Degree. Lulea, Sweden: Department of Arts, Communication and Education, Luleå University of Technology.The purpose of this study was to describe, analyze and understand how teachers in the preschool environment, work indoors to support children's language development. In order to answer our purpose, we used a qualitative research method in the form of interviews and literature studies. In our study we interviewed four active educators in four kindergartens in a small community in northern Sweden.The results of this study showed that the informants had language development in mind when they designed the physical environment of the preschool. The informants mention not often furnishing as an important factor, but instead is focus on that there should be access to social venues where children can perform common activities. Special education teachers have an important role in early childhood education, and several of the informants are turning to them to get tips and advice on how they can support children with language differences. It is important to make it pleasurable and interesting for the kids when the teacher is working to support children with language discrepancy. The study revealed that teachers used primarily sago bags, pictures, songs, rhymes when they want to focus extra on language development, this material is widely used in shared collections. The informants in the study felt that communication between children and adults is an important part of language development for children with language and without deviation. We could see the study that some kindergartens are more advanced in the process of language development. One preschool has come so far in their development that they have pioneered the use of ICT to develop the language of the children. Validerat; 20130117 (global_studentproject_submitter)